Introduction to fractions. - Harper & Row, Publishers (White Plains, N.Y. : Center for Humanities, 1979)
Topics covered include terms of fractions, reduction to lowest terms, conversion to higher terms, least common multiple, and least common denominator.
"The skills group."
Also issued with sound accompaniment on disc.
Keywords: Fractions